2021
DOI: 10.3389/fpls.2020.609977
|View full text |Cite
|
Sign up to set email alerts
|

Adding Far-Red to Red-Blue Light-Emitting Diode Light Promotes Yield of Lettuce at Different Planting Densities

Abstract: The economic viability and energy use of vertical farms strongly depend on the efficiency of the use of light. Increasing far-red radiation (FR, 700–800 nm) relative to photosynthetically active radiation (PAR, 400–700 nm) may induce shade avoidance responses including stem elongation and leaf expansion, which would benefit light interception, and FR might even be photosynthetically active when used in combination with PAR. The aims of this study are to investigate the interaction between FR and planting densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 27 publications
(26 reference statements)
2
32
1
Order By: Relevance
“…In our experiment, the addition of FR to the spectrum did not result in a yield increase. However, Jin et al [30] showed an increase in shoot weight when FR radiation was added to B+R radiation in lettuce 28 days after transplanting and Meng and Runkle [31] in lettuce and basil seedlings, a phenomenon that could be associated with faster leaf area expansion, which would ultimately result in increased light interception [30]. Possibly, in the current experiment, given that microgreens are harvested at early stage, the beneficial effects on leaf elongation induced by FR radiation were negligible, and therefore did not allow for increased light interception.…”
Section: Yieldmentioning
confidence: 97%
“…In our experiment, the addition of FR to the spectrum did not result in a yield increase. However, Jin et al [30] showed an increase in shoot weight when FR radiation was added to B+R radiation in lettuce 28 days after transplanting and Meng and Runkle [31] in lettuce and basil seedlings, a phenomenon that could be associated with faster leaf area expansion, which would ultimately result in increased light interception [30]. Possibly, in the current experiment, given that microgreens are harvested at early stage, the beneficial effects on leaf elongation induced by FR radiation were negligible, and therefore did not allow for increased light interception.…”
Section: Yieldmentioning
confidence: 97%
“…Also, assimilates in the vegetative organs gradually move to the grain in the late growth stage (Yang et al, 1997 ; Ma et al, 2008 ; Gao et al, 2017 ). Modern maize grain yield improvements are highly dependent on increasing plant density while enabling the plants to intercept more solar radiation (Liu et al, 2017 , 2021c ; Hou et al, 2020 ), and planting density affects light quality and other environmental factors that influence the yield as well (Jin et al, 2020 ). Also, planting density has important effects on maize dry matter partitioning between vegetative and reproductive organs (Wei et al, 2019 ), as planting density increases, the numbers of vegetative organs increase while that of reproductive organs decrease (Liu et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…It could also be possible that the application period was too short, as longer tomato experiments with the same experimental setup as described in our study resulted in a higher light use efficiency and higher yields in favor of the LED treatment [13]. Other research groups added far-red with an intensity of 52 µmol m −2 s −1 [28] or 26 µmol m −2 s −1 [29] to red-blue LEDs, which increased the plant biomass production of lettuce. The far-red radiation caused by the new LED fixture in the present study (4 µmol m −2 s −1 ) was not sufficient to achieve the same effects.…”
Section: Plant Growth and Yieldmentioning
confidence: 88%